2020
DOI: 10.1371/journal.pntd.0008621
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological models for predicting Ross River virus in Australia: A systematic review

Abstract: Ross River virus (RRV) is the most common and widespread arbovirus in Australia. Epidemiological models of RRV increase understanding of RRV transmission and help provide early warning of outbreaks to reduce incidence. However, RRV predictive models have not been systematically reviewed, analysed, and compared. The hypothesis of this systematic review was that summarising the epidemiological models applied to predict RRV disease and analysing model performance could elucidate drivers of RRV incidence and trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 85 publications
0
16
0
Order By: Relevance
“…There are multiple environmental, meteorological, biological, socioeconomic, geographical, host, and vector components which contribute to the transmission dynamics of RRV [ 10 , 36 , 44 ]. Factors included in the predictive models developed here use meteorological data which are readily accessible without the need for extensive data requests or data gathering processes, allowing for the approach used here to be easily replicated and integrated into predictive disease surveillance systems.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are multiple environmental, meteorological, biological, socioeconomic, geographical, host, and vector components which contribute to the transmission dynamics of RRV [ 10 , 36 , 44 ]. Factors included in the predictive models developed here use meteorological data which are readily accessible without the need for extensive data requests or data gathering processes, allowing for the approach used here to be easily replicated and integrated into predictive disease surveillance systems.…”
Section: Discussionmentioning
confidence: 99%
“…However, a caveat to this approach is the omission of variables that have previously been found to be important in the transmission of RRV among regions studied here. For example, variation in tide heights, river flow and height, and climatic conditions (e.g., Southern Oscillation Index) which are known to be associated with increases in mosquito breeding and potential host movement which can lead to greater RRV transmission [ 1 , 2 , 10 , 17 , 18 , 43 ]. Moreover, mosquito and host species vary between the LGAs examined here.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is further evident by the fact that studies showed varying results [ 47 , 53 , 54 , 108 , 109 ]. Integration of statistical, mechanistic, and non-linear mixed models, for example characterization of non-linear thermal responses to identify transmission temperature optima and limits [ 107 ], would improve model prediction (recently reviewed in [ 110 , 111 ]).…”
Section: Future Forecastmentioning
confidence: 99%